Price Level Determinacy and Monetary Policy under a Balanced-Budget Requirement - Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 1998)
This paper analyzes the implications of a balanced-budget fiscal policy rule for price-level determination in a cash-in-advance economy under three alternative monetary policy regimes. It shows that the price level is indeterminate under a nominal interest rate peg and determinate under a money growth rate peg. Under a feedback rule that sets the nominal interest rate as a non-negative and non-decreasing function of the inflation rate, the price level is indeterminate for both low and high values of the inflation elasticity of the feedback rule and determinate for intermediate values. We also study balanced-budget rules that allow for bounded secondary surpluses or deficits. Comparing our results to those emphasized in the fiscal theory of the price level, it becomes clear that a key consideration for price-level determination is whether fiscal policy is specified as an exogenous sequence of primary surpluses/deficits or, alternatively, as an exogenous sequence of secondary surpluses/deficits.
Keywords: E31; E52; E63; 330; balanced-budget rules; fiscal theory of the price level; monetary policy